PEMBUATAN ALAT EVALUASI PEMBELAJARAN PIYAMA PRIA - Endah Perina; Astuti Astuti (Fesyen Perspektif, 2016)
Preliminary studies were performed on some vocational training institutes (LPK) obtained information that hasn’t been assessment guidelines for assessing man pajamas products. This study aims to produce a learning evaluation instrument that can be used as a standard / reference in assessing the learning outcomes of students in the form of man pajamas products. The learning evaluation instrument of man pajamas is the assessment format of man pajamas products which arranged in detail, and there are criterias for the assessment parts of man pajamas products. The method used in this study through the stages of introduction study, making of learning evaluation instrument, validity test and the revision stage. The feasibility of the use of learning evaluation instrument is known from the validity of the test results from matter experts and evaluation expert. The test results showed that the validity of the learning evaluation instrument of man pajamas which has been made are included in category "feasible" to be used by the average percentage of 100% of the matter experts and 94.58% of the evaluation expert. The learning evaluation instrument of man pajamas has been made this expected to become the standard reference (standard) in assessing student learning outcomes are man pajamas products at various institutions / agencies and educational training.